Strong Institutional Objectivity: Designing Knowledge Systems Beyond Individual Bias and Power Asymmetry - Zhang, Michael Che (Advances in Social Sciences Research Journal, 2025)
Recent developments in cognitive neuroscience, particularly predictive processing models, demonstrate that human perception operates through active inference rather than passive observation (Clark, 2016; Friston, 2010). This finding, combined with previous research on heuristics and biases, challenges the empirical viability of the traditionally conceived version of individual-level objectivity. (Kahneman, 2011; Hohwy, 2013). Simultaneously, digital systems exhibit measurable tendencies toward homophily reinforcement and selective exposure amplification that worsen the information environment (Pariser, 2011; Bakshy et al., 2015). Therefore, this paper develops a framework of strong institutional objectivity that synthesizes insights from predictive processing, social epistemology, and power analysis to reconceptualize objectivity as an emergent institutional property rather than an individual action.. Through comparative case analysis of scientific reform initiatives and algorithmic mediation systems, I identify specific institutional design features that demonstrably improve error detection and correction rates while addressing structural exclusions that compromise knowledge production. The analysis yields testable propositions about the interaction between procedural controls and participation structures in determining epistemic outcomes, providing both a theoretical synthesis and an empirically grounded model for designing knowledge systems that achieve reliability through institutional mechanisms.